Improving the Relationship between Welfare Economics and Ethics - Carmen Pagliari (Annales Etyka w Życiu Gospodarczym, 2017)
In this essay, the essential aspects of Welfare Economics are summarized in order to analyse the possible links with Ethics, and consequently to provide useful suggestions for Economic Policy. The Introduction contains the principles of neoclassical Welfare Economics, without considering the circumstances in which the so‑called failures of competitive markets occur. The second part of this paper contains a description of two possible solutions to the problem concerning the integration of Welfare Economics and Ethics. The first solution is the determination of the optimal combination of general competitive equilibrium principles and social ethics ones, without removing the theoretical structure of Welfare Economics. This first proposal, while retaining some economic liberalism principles, assigns a central role to the government, which is delegated to superimpose on the Pareto criterion a distributive justice rule. Another solution, which is suggested by Sen, is essentially directed to modify Welfare Economics by ethical criteria aimed at improving every individual deprivation, and it is based on the distinction between the two concepts of ‘utility’ and ‘agency’. We also proposed exploiting the original considerations written by Smith about social aspects as a useful integration and support to Sen’s approach.